2020
DOI: 10.3390/jmse8060471
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomic Analyses of Wild and Farmed Striped Catfish Pangasianodon Hypophthalmus in the Lower Mekong River

Abstract: The striped catfish Pangasianodon hypophthalmus is an important freshwater fish cultured in many countries where the collection of wild brooders is still widely practiced. Global farming development of this species makes use of significant natural resources that pose challenges for the genetic diversity of striped catfish. Hence, this study aims to conduct a systematic genetic diversity assessment of wild and farmed catfish stocks collected from four major pangasius-farming countries, using a new genotyping by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Wild marine fish species Pangasianodon Hypophthalmus and Oreochromis niloticus have previously shown genomewide SNP heterozygosity of 0.04-0.60. In this study, the SNP heterozygosity of the wild population was found to be 0.335, which is comparable to that of the wild O. niloticus population [40,41]. However, Li et al showed that the average heterozygosity of SNP in wild roughskin sculpin was 0.121, unlike the results of this study [7].…”
Section: Discussioncontrasting
confidence: 69%
“…Wild marine fish species Pangasianodon Hypophthalmus and Oreochromis niloticus have previously shown genomewide SNP heterozygosity of 0.04-0.60. In this study, the SNP heterozygosity of the wild population was found to be 0.335, which is comparable to that of the wild O. niloticus population [40,41]. However, Li et al showed that the average heterozygosity of SNP in wild roughskin sculpin was 0.121, unlike the results of this study [7].…”
Section: Discussioncontrasting
confidence: 69%
“…The DArTseq TM was based on the genome complexity reduction method in combination with high throughput next-generation sequencing using Illumina platform. The sequencing protocol including choice of restricted enzymes and library preparation was optimized for striped catfish (Pangasianodon DarTseq 1.0) using 96 independent DNA samples of striped catfish in our earlier study ( Vu et al 2020 ). Briefly, the PstI-SphI method ( Kilian et al 2012 ) was used and the compatible adaptors were designed to include Illumina flow-cell attachment sequence, sequencing primer sequence, and capturing variant length of barcode regions ( Elshire et al 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…DArTseq™ represents a combination of genome complexity reduction methods and high throughput sequencing platforms ( Kilian et al, 2012 ). A detailed description regarding selections of restricted enzymes, PCR reactions, library preparations and sequencing is given in our earlier studies ( Nguyen et al, 2018a ; Nguyen et al, 2018b ; Nguyen et al, 2020b ; Vu et al, 2020 ). Briefly, sequences generated from each lane were processed using proprietary DArTseq pipelines.…”
Section: Methodsmentioning
confidence: 99%